A kind of ANF / CNT gel powder modified cement paste material
By combining carbon nanotubes with aramid nanofibers using alkali modification and ultrasonic treatment methods in cement, an interpenetrating network structure is formed, which solves the problem of volume shrinkage and cracking of cement-based materials, and improves the mechanical properties and shrinkage resistance of cement. ability to extend its service life.
Patent Information
- Application Number
- CN202411346695.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-26
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2044-09-26
AI Technical Summary
Traditional cement-based materials have volume shrinkage due to hydration reaction, temperature changes and drying, causing tensile stress and cracking problems. The existing nanocellulose gel has poor mechanical properties and is difficult to meet the requirements of high-strength cement. Moreover, aramid nano Fiber aerogel has low mechanical strength and is only suitable for low-strength insulation putty fields.
Using alkaline liquid modification and ultrasonic treatment methods, carbon nanotubes are added to the aramid nanofiber dispersion to form an interpenetrating network structure, improve the mechanical strength and toughness of the gel, reduce the self-drying and shrinkage of cement, and enhance its shrinkage resistance. .
Through the cross-penetration and mechanical entanglement of carbon nanotubes and aramid nanofibers, a high-density interface is formed, which improves the porosity and water retention properties of the gel, significantly reduces the risk of shrinkage and cracking of cement, and enhances the durability of cement and Structural reliability.
Smart Images

Figure CN118878287B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of cement materials, and in particular relates to an ANF / CNT gel powder modified cement paste material. Background Art
[0002] Cement-based materials have become the world's largest and most widely used construction materials due to their simple preparation process, low cost and ease of use. However, with the upgrading of industrial structure and changes in social needs, the shortcomings of traditional cement-based materials have been continuously magnified. The weak bonding between hydration products and the disordered distribution of pore structures cause cement-based materials to exhibit defects such as large shrinkage, poor deformation ability and low toughness. These inherent defects cause cracking, spalling and erosion, which significantly affect the life and application of cement-based materials in modern buildings.
[0003] Traditionally, the method to improve the shrinkage defects of cement-based materials and increase their strength and toughness is mainly based on material composites, that is, taking silicate cement as the matrix, adding other organic, inorganic, metal and other materials to construct cement-based composite materials to achieve performance optimization. Different composite materials and structural morphologies have different degrees and mechanisms of performance enhancement on cement-based materials. For example, fiber-reinforced cement can effectively inhibit the expansion of cracks by utilizing the interface effect between fibers and cement matrix, and significantly improve the mechanical properties of cement-based materials such as tensile strength, bending strength and toughness; various nanomaterials, such as carbon nanotubes, graphene, and silica particles, can improve the mechanical properties of cement-based materials while also improving the water permeability and conductivity of cement matrix through the principle of second phase strengthening; polymer emulsions and other polymer materials can effectively improve the pore structure of cement matrix by utilizing the principle of simultaneous hydration reaction and polymer film formation, and can also prepare functional building materials such as heat insulation and fire prevention while improving strength.
[0004] However, cement-based materials usually shrink in volume due to hydration reaction, temperature change and drying. After the cement component is constrained, the volume shrinkage produced will cause tensile stress inside the cement and even cause cement cracking. With the rapid development of the construction industry, the cracking of cement structures has become a problem worthy of attention in the field of civil engineering. At present, in order to reduce or compensate for the shrinkage of cement, methods such as adding expansion agents, adding shrinkage reducers or using cementitious materials with low hydration heat release can be used to reduce the heat release of cement hydration. Among them, the use of adding cementitious materials as water retaining agents is currently the main method to solve the shrinkage of cement and reduce the corresponding shrinkage cracking. For example, patents such as CN111892378A, CN 112321213A, and CN 116120018A all use nanocellulose as a gel frame for mortar. However, nanocellulose gel has poor mechanical properties and is difficult to meet the use requirements of high-strength cement. It is mainly used in the field of thermal insulation mortar. Although CN116694126A prepared aramid nanofiber aerogel, it used an in-situ polymerization process to prepare aramid nanofibers, resulting in a small fiber aspect ratio and poor mechanical properties. The mechanical strength of the prepared aerogel is low, and it can only be applied to the field of low-strength thermal insulation putty to achieve the technical effect of heat insulation. Therefore, how to improve these problems existing in maintenance and improve the mechanical properties of cement on the basis of preventing cement shrinkage and cracking has become the focus and hotspot of current research. Summary of the invention
[0005] In view of the problems existing in the prior art, the present invention provides an ANF / CNT gel powder modified cement paste material. Carbon nanotube and aramid nanofiber gel powder can reduce self-drying shrinkage through water compensation, promote hydration, and improve the performance of cement, especially reduce the risk of cement shrinkage cracking. After the cement is poured, its structure can be maintained, thereby increasing the anti-shrinkage ability of the cement itself, reducing the phenomenon of early deformation, and thus improving the durability and structural reliability of the cement.
[0006] An ANF / CNT gel powder modified cement paste material, wherein the cement paste comprises cement and ANF / CNT gel powder;
[0007] The preparation method of the ANF / CNT gel powder comprises the following steps:
[0008] (1) placing aramid fiber into a reaction kettle containing alkali and dimethyl sulfoxide and stirring the mixture to prepare an aramid nanofiber dispersion;
[0009] (2) adding carbon nanotubes to the aramid nanofiber dispersion, dispersing by ultrasonication, and then adding deionized water to obtain a mixed solution; the mass ratio of the aramid fiber to the carbon nanotubes is 1:(0-1); wherein the mass of the carbon nanotubes is not 0;
[0010] (3) preparing an initial hydrogel by subjecting the mixed solution to a steam bath; and exchanging the solvent of the initial hydrogel with deionized water to obtain a hydrogel;
[0011] (4) The hydrogel is freeze-dried and crushed to obtain ANF / CNT gel powder.
[0012] In previous work, the inventors found that the use of aramid nanofibers as the base material of the gel greatly enhances its mechanical properties compared to ordinary resin-type and nanocellulose-type gels. However, the mechanical properties of pure aramid nanofiber gels are insufficient, and the shrinkage after water release is large. More importantly, although the aramid nanofibers prepared by the alkali / DMSO immersion method have a large aspect ratio, the fiber bundles are easily merged in the aqueous solution, resulting in fiber agglomeration, which affects the porosity and water retention of the gel. Moreover, as an organic gel material, the aramid nanofiber gel will shrink in volume after water release, which seriously affects the safety, stability and durability of the structure. In order to improve the structural stability of the gel, the inventors first added solid, hollow or core-shell inorganic nanoparticles to the mixed solution of alkali and dimethyl sulfoxide of aramid nanofibers, and then added water; compared with first adding water to the aramid nanofiber dispersion and then adding modified inorganic nanoparticles, the dispersion properties of the nanofibers can be more effectively improved.
[0013] However, there are certain limitations in preventing the aggregation of aramid nanofibers by using inorganic particles. The zero-dimensional structure has poor particle isolation, and the loading of inorganic nanoparticles inside the gel will cause the gel to shrink to a certain extent, which is not conducive to the formation of a multi-porous structure. In addition, the direct use of inorganic nanoparticles as a modification agent for aramid nanofibers will affect the flow properties of cement. Cement paste is usually required to have higher fluidity and is used to fill or seal cracks, or as an adhesive during construction to ensure its firm connection. Due to the poor control of the proportion of cement paste components, improper operation can easily lead to unsatisfactory performance of the repaired cement structure.
[0014] In order to prepare high-performance cement paste materials, the present invention modifies aramid nanofibers by adding carbon nanotubes to them, which can greatly improve the strength and toughness of gel composite materials. The aspect ratio and surface area of carbon nanotubes are large, and there is a strong van der Waals attraction between the tubes. Directly adding carbon nanotubes into the aramid nanofiber aqueous solution can easily cause the carbon nanotubes to entangle with each other and agglomerate. The present invention adopts a method combining alkali solution modification and ultrasonic treatment to add carbon nanotubes to the aramid nanofiber dispersion and ultrasonically disperse them. By ultrasonic treatment in alkali solution, active groups such as hydroxyl and carboxyl are introduced on the surface of the carbon nanotubes. Due to the presence of surface active groups, the modified carbon nanotubes introduce charge repulsion between the carbon nanotubes on the one hand, and on the other hand, improve the hydrophilicity of the carbon nanotubes, thereby improving the dispersibility of the carbon nanotubes in the aqueous solution in the subsequent process. The surface of the aramid nanofibers prepared by the alkali method is relatively rough, with a diameter between 20nm-70nm and a length of about 10μm, and its diameter can be adjusted by adjusting the soaking process parameters; carbon nanotubes are common carbon nanomaterials, with a diameter of usually 20-80nm and a length of about 1-10μm. Under the action of ultrasound, the gradually dispersed carbon nanotubes can effectively isolate and disperse the aramid nanofibers prepared by the alkali / DMSO soaking method, so that the carbon nanotubes and aramid nanofibers are entangled with each other to form an interpenetrating network structure. Through the mutual cross-penetration and mechanical entanglement between the carbon nanotubes and the aramid nanofibers, the interpenetrating network structure can improve the mechanical strength of the material and enhance its ability to resist external forces. Moreover, the interpenetrating network structure of carbon nanotubes and aramid nanofibers can form a high-density interface between the fibers, which further improves the porosity of the gel and improves its water release shrinkage, promotes the stability of the gel structure, and achieves the improvement of the mechanical properties and shrinkage resistance of cement.
[0015] Furthermore, the stirring rate in step (1) is 400-600 r / min.
[0016] Furthermore, the aramid fiber is Kevlar fiber produced by DuPont.
[0017] Furthermore, in step (1), the alkali is sodium hydroxide or potassium hydroxide; the ratio of the aramid fiber, the alkali and the dimethyl sulfoxide is 1 g: (1-2) g: (400-500) mL; and the stirring is carried out at room temperature for 4-8 days.
[0018] Furthermore, in step (2), the mass ratio of aramid fiber to carbon nanotube is 1:(0.2-0.5); the carbon nanotube is a single-walled carbon nanotube or a multi-walled carbon nanotube. As the amount of carbon nanotube added increases, the isolation and toughening effect weakens, and the carbon nanotube agglomeration phenomenon on the surface becomes more serious. This part of carbon nanotube only plays a role of mass filling and cannot be effectively composited with aramid nanofiber. Too many carbon nanotubes may produce more cross-linking points, which greatly increases the cross-linking density of the composite gel, resulting in a decrease in the water absorption and water retention properties of the gel powder.
[0019] Furthermore, in the step (2), the frequency of ultrasonic dispersion is 60-80kHz, the ultrasonic time is 2-4h; the ratio of aramid fiber to deionized water is 1g: (250-300)mL. The shear force and impact force generated by the high-frequency vibration of ultrasonic dispersion are used to quickly disperse the carbon nanotubes and aramid nanofibers to a uniform state in a short time. Compared with the traditional stirring and grinding method, the dispersion efficiency is higher, the processing time is shorter, and the carbon nanotubes and aramid nanofibers can be evenly dispersed in the liquid medium, avoiding the aggregation and deposition of the carbon nanotubes and aramid nanofibers, so that the carbon nanotubes and aramid nanofibers are entangled with each other to form an interpenetrating network structure. Moreover, under the action of ultrasound, the aramid nanofibers are further peeled off in the alkali / DMSO dispersion, a bifurcated structure appears, and holes and cracks appear on the fibers, further improving the water retention performance of the gel.
[0020] Furthermore, in step (3), the steam bath is an acetic acid steam bath, a hydrochloric acid steam bath, a formic acid steam bath or a nitric acid steam bath, and the steam bath treatment time is 6-10 hours. The fibers in the solution are protonated by the vapor of the protonated solvent, and the gel preparation process is simple and efficient, and a physical gel material with a rich network structure can be successfully prepared under low concentration conditions. The complex cross-linking process in the direct preparation of gel compounds by the traditional method is effectively avoided, and the refinement and stability of the structure are improved.
[0021] Furthermore, the freeze-drying temperature in step (4) is -20°C to -60°C.
[0022] Furthermore, the cement paste also includes water and a water reducing agent; the mass ratio of cement, ANF / CNT gel powder, water reducing agent and water is 100: (0.1-2): (0.1-1): (40-50).
[0023] Furthermore, the water reducer is a polycarboxylate water reducer.
[0024] Beneficial effects: The carbon nanotubes are added to the aramid nanofiber dispersion by combining alkali modification and ultrasonic treatment. Under the action of ultrasound, the gradually dispersed modified carbon nanotubes can effectively isolate and disperse the aramid nanofibers prepared by the alkali / DMSO immersion method, so that the carbon nanotubes and the aramid nanofibers are entangled with each other to form an interpenetrating network structure. Through the mutual cross-penetration and mechanical entanglement between the carbon nanotubes and the aramid nanofibers, the interpenetrating network structure can improve the mechanical strength of the material and enhance its ability to resist external forces. Moreover, the interpenetrating network structure of the carbon nanotubes and the aramid nanofibers can form a high-density interface between the fibers, and on the basis of further improving the porosity of the gel, it also improves its water release shrinkage, promotes the stability of the gel structure, and realizes the improvement of the mechanical properties and shrinkage resistance of the cement. Moreover, after being corroded by alkali, the internal cavity of the carbon nanotubes will also retain a part of water, so that the carbon nanotubes and aramid nanofiber gel powders can give full play to the role of the internal curing agent, and minimize the self-drying shrinkage of the cement by increasing the relative humidity inside the cement. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 This is a transmission electron microscopy image of the ANF / CNT gel powder prepared in Example 7;
[0026] Figure 2 This is a test diagram of the water retention performance of the ANF / CNT gel powder prepared in Example 1-5;
[0027] Figure 3 This is a test chart of the water retention performance of the ANF / CNT gel powder prepared in Examples 6-9 and Comparative Examples 1-2. DETAILED DESCRIPTION
[0028] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme of the present invention will be clearly and completely described in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the described embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Unless otherwise defined, the technical terms or scientific terms used herein should be the common meanings understood by people with general skills in the field to which the present invention belongs. Among them, the aramid fiber in the following embodiments and comparative examples is DuPont Kevlar fiber; carbon nanotubes are multi-walled carbon nanotubes; cement is silicate cement; and water reducer is polycarboxylic acid water reducer.
[0029] Example 1
[0030] An ANF / CNT gel powder modified cement paste material, wherein the mass ratio of cement, ANF / CNT gel powder, water reducing agent and water in the cement paste is 100:1:0.6:40;
[0031] The preparation method of the ANF / CNT gel powder comprises the following steps:
[0032] (1) placing aramid fiber in a reaction kettle containing alkali and dimethyl sulfoxide, stirring evenly, and preparing an aramid nanofiber dispersion; the alkali is potassium hydroxide; the ratio of the aramid fiber, the alkali and the dimethyl sulfoxide is 1 g:1 g:400 mL; stirring is performed at room temperature for 8 days at a stirring rate of 500 r / min;
[0033] (2) Add carbon nanotubes to the aramid nanofiber dispersion, disperse by ultrasonication, and then add deionized water to obtain a mixed solution; the mass ratio of aramid fiber to carbon nanotubes is 1:0.2; the frequency of ultrasonic dispersion is 60 kHz, and the ultrasonic time is 3 h; the ratio of aramid fiber to deionized water is 1 g:250 mL;
[0034] (3) preparing an initial hydrogel by subjecting the mixed solution to a steam bath; and exchanging the solvent of the initial hydrogel with deionized water to obtain a hydrogel; the steam bath is an acetic acid steam bath, and the steam bath treatment time is 6 hours;
[0035] (4) The hydrogel was freeze-dried at -40 °C and crushed to obtain ANF / CNT gel powder.
[0036] Example 2
[0037] An ANF / CNT gel powder modified cement paste material, wherein the mass ratio of cement, ANF / CNT gel powder, water reducing agent and water in the cement paste is 100:1:0.4:50;
[0038] The preparation method of the ANF / CNT gel powder comprises the following steps:
[0039] (1) placing aramid fiber in a reaction kettle containing alkali and dimethyl sulfoxide, stirring evenly, and preparing an aramid nanofiber dispersion; the alkali is potassium hydroxide; the ratio of the aramid fiber, the alkali and the dimethyl sulfoxide is 1 g:2 g:500 mL; stirring is performed at room temperature for 8 days at a stirring rate of 500 r / min;
[0040] (2) Add carbon nanotubes to the aramid nanofiber dispersion, disperse by ultrasonication, and then add deionized water to obtain a mixed solution; the mass ratio of aramid fiber to carbon nanotubes is 1:0.5; the frequency of ultrasonic dispersion is 80 kHz, and the ultrasonic time is 3 h; the ratio of aramid fiber to deionized water is 1 g:300 mL;
[0041] (3) preparing an initial hydrogel by subjecting the mixed solution to a steam bath; and exchanging the solvent of the initial hydrogel with deionized water to obtain a hydrogel; the steam bath is a hydrochloric acid steam bath, and the steam bath treatment time is 10 hours;
[0042] (4) The hydrogel was freeze-dried at -40 °C and crushed to obtain ANF / CNT gel powder.
[0043] Example 3
[0044] An ANF / CNT gel powder modified cement paste material, wherein the mass ratio of cement, ANF / CNT gel powder, water reducing agent and water in the cement paste is 100:1:0.6:50;
[0045] The preparation method of the ANF / CNT gel powder comprises the following steps:
[0046] (1) placing aramid fiber in a reaction kettle containing alkali and dimethyl sulfoxide, stirring evenly, and preparing an aramid nanofiber dispersion; the alkali is potassium hydroxide; the ratio of the aramid fiber, the alkali and the dimethyl sulfoxide is 1 g:1 g:500 mL; stirring is performed at room temperature for 8 days at a stirring rate of 500 r / min;
[0047] (2) Add carbon nanotubes to the aramid nanofiber dispersion, disperse by ultrasonication, and then add deionized water to obtain a mixed solution; the mass ratio of aramid fiber to carbon nanotubes is 1:0.3; the frequency of ultrasonic dispersion is 80 kHz, and the ultrasonic time is 3 h; the ratio of aramid fiber to deionized water is 1 g:300 mL;
[0048] (3) preparing an initial hydrogel by subjecting the mixed solution to a steam bath; and exchanging the solvent of the initial hydrogel with deionized water to obtain a hydrogel; the steam bath is a hydrochloric acid steam bath, and the steam bath treatment time is 10 hours;
[0049] (4) The hydrogel was freeze-dried at -40 °C and crushed to obtain ANF / CNT gel powder.
[0050] Example 4
[0051] An ANF / CNT gel powder modified cement paste material, wherein the mass ratio of cement, ANF / CNT gel powder, water reducing agent and water in the cement paste is 100:1:0.4:40;
[0052] The preparation method of the ANF / CNT gel powder comprises the following steps:
[0053] (1) placing aramid fiber in a reaction kettle containing alkali and dimethyl sulfoxide, stirring evenly, and preparing an aramid nanofiber dispersion; the alkali is potassium hydroxide; the ratio of the aramid fiber, the alkali and the dimethyl sulfoxide is 1 g:2 g:400 mL; stirring is performed at room temperature for 8 days at a stirring rate of 500 r / min;
[0054] (2) Add carbon nanotubes to the aramid nanofiber dispersion, disperse by ultrasonication, and then add deionized water to obtain a mixed solution; the mass ratio of aramid fiber to carbon nanotubes is 1:0.4; the frequency of ultrasonic dispersion is 60 kHz, and the ultrasonic time is 3 h; the ratio of aramid fiber to deionized water is 1 g:300 mL;
[0055] (3) preparing an initial hydrogel by subjecting the mixed solution to a steam bath; and exchanging the solvent of the initial hydrogel with deionized water to obtain a hydrogel; the steam bath is an acetic acid steam bath, and the steam bath treatment time is 6 hours;
[0056] (4) The hydrogel was freeze-dried at -40 °C and crushed to obtain ANF / CNT gel powder.
[0057] Example 5
[0058] An ANF / CNT gel powder modified cement paste material, wherein the mass ratio of cement, ANF / CNT gel powder, water reducing agent and water in the cement paste is 100:1:0.5:43;
[0059] The preparation method of the ANF / CNT gel powder comprises the following steps:
[0060] (1) placing aramid fiber in a reaction kettle containing alkali and dimethyl sulfoxide, stirring evenly, and preparing an aramid nanofiber dispersion; the alkali is potassium hydroxide; the ratio of the aramid fiber, the alkali and the dimethyl sulfoxide is 1 g:1.2 g:430 mL; stirring is performed at room temperature for 8 days at a stirring rate of 500 r / min;
[0061] (2) Add carbon nanotubes to the aramid nanofiber dispersion, disperse by ultrasonication, and then add deionized water to obtain a mixed solution; the mass ratio of aramid fiber to carbon nanotubes is 1:0.3; the frequency of ultrasonic dispersion is 65 kHz, and the ultrasonic time is 3 h; the ratio of aramid fiber to deionized water is 1 g:260 mL;
[0062] (3) preparing an initial hydrogel by subjecting the mixed solution to a steam bath; and exchanging the solvent of the initial hydrogel with deionized water to obtain a hydrogel; the steam bath is an acetic acid steam bath, and the steam bath treatment time is 7 hours;
[0063] (4) The hydrogel was freeze-dried at -40 °C and crushed to obtain ANF / CNT gel powder.
[0064] Example 6
[0065] An ANF / CNT gel powder modified cement paste material, wherein the mass ratio of cement, ANF / CNT gel powder, water reducing agent and water in the cement paste is 100:1:0.5:48;
[0066] The preparation method of the ANF / CNT gel powder comprises the following steps:
[0067] (1) placing aramid fiber in a reaction kettle containing alkali and dimethyl sulfoxide, stirring evenly, and preparing an aramid nanofiber dispersion; the alkali is potassium hydroxide; the ratio of the aramid fiber, the alkali and the dimethyl sulfoxide is 1 g:1.8 g:490 mL; stirring is performed at room temperature for 8 days at a stirring rate of 500 r / min;
[0068] (2) Add carbon nanotubes to the aramid nanofiber dispersion, disperse by ultrasonication, and then add deionized water to obtain a mixed solution; the mass ratio of aramid fiber to carbon nanotubes is 1:0.4; the frequency of ultrasonic dispersion is 75 kHz, and the ultrasonic time is 3 h; the ratio of aramid fiber to deionized water is 1 g:280 mL;
[0069] (3) preparing an initial hydrogel by subjecting the mixed solution to a steam bath; and exchanging the solvent of the initial hydrogel with deionized water to obtain a hydrogel; the steam bath is a hydrochloric acid steam bath, and the steam bath treatment time is 9 hours;
[0070] (4) The hydrogel was freeze-dried at -40 °C and crushed to obtain ANF / CNT gel powder.
[0071] Example 7
[0072] An ANF / CNT gel powder modified cement paste material, wherein the mass ratio of cement, ANF / CNT gel powder, water reducing agent and water in the cement paste is 100:1:0.5:46;
[0073] The preparation method of the ANF / CNT gel powder comprises the following steps:
[0074] (1) placing aramid fiber in a reaction kettle containing alkali and dimethyl sulfoxide, stirring evenly, and preparing an aramid nanofiber dispersion; the alkali is potassium hydroxide; the ratio of the aramid fiber, the alkali and the dimethyl sulfoxide is 1 g:1.6 g:450 mL; stirring is performed at room temperature for 8 days at a stirring rate of 500 r / min;
[0075] (2) Add carbon nanotubes to the aramid nanofiber dispersion, disperse by ultrasonication, and then add deionized water to obtain a mixed solution; the mass ratio of aramid fiber to carbon nanotubes is 1:0.4; the frequency of ultrasonic dispersion is 70 kHz, and the ultrasonic time is 3 h; the ratio of aramid fiber to deionized water is 1 g:300 mL;
[0076] (3) preparing an initial hydrogel by subjecting the mixed solution to a steam bath; and exchanging the solvent of the initial hydrogel with deionized water to obtain a hydrogel; the steam bath is an acetic acid steam bath, and the steam bath treatment time is 8 hours;
[0077] (4) The hydrogel was freeze-dried at -40 °C and crushed to obtain ANF / CNT gel powder.
[0078] Example 8
[0079] An ANF / CNT gel powder modified cement paste material, wherein the mass ratio of cement, ANF / CNT gel powder, water reducing agent and water in the cement paste is 100:1:0.5:46;
[0080] The preparation method of the ANF / CNT gel powder comprises the following steps:
[0081] (1) placing aramid fiber in a reaction kettle containing alkali and dimethyl sulfoxide, stirring evenly, and preparing an aramid nanofiber dispersion; the alkali is potassium hydroxide; the ratio of the aramid fiber, the alkali and the dimethyl sulfoxide is 1 g:1.6 g:450 mL; stirring is performed at room temperature for 8 days at a stirring rate of 500 r / min;
[0082] (2) Add carbon nanotubes to the aramid nanofiber dispersion, disperse by ultrasonication, and then add deionized water to obtain a mixed solution; the mass ratio of aramid fiber to carbon nanotubes is 1:0.1; the frequency of ultrasonic dispersion is 70 kHz, and the ultrasonic time is 3 h; the ratio of aramid fiber to deionized water is 1 g:300 mL;
[0083] (3) preparing an initial hydrogel by subjecting the mixed solution to a steam bath; and exchanging the solvent of the initial hydrogel with deionized water to obtain a hydrogel; the steam bath is an acetic acid steam bath, and the steam bath treatment time is 8 hours;
[0084] (4) The hydrogel was freeze-dried at -40 °C and crushed to obtain ANF / CNT gel powder.
[0085] Example 9
[0086] An ANF / CNT gel powder modified cement paste material, wherein the mass ratio of cement, ANF / CNT gel powder, water reducing agent and water in the cement paste is 100:1:0.5:46;
[0087] The preparation method of the ANF / CNT gel powder comprises the following steps:
[0088] (1) placing aramid fiber in a reaction kettle containing alkali and dimethyl sulfoxide, stirring evenly, and preparing an aramid nanofiber dispersion; the alkali is potassium hydroxide; the ratio of the aramid fiber, the alkali and the dimethyl sulfoxide is 1 g:1.6 g:450 mL; stirring is performed at room temperature for 8 days at a stirring rate of 500 r / min;
[0089] (2) Add carbon nanotubes to the aramid nanofiber dispersion, disperse by ultrasonication, and then add deionized water to obtain a mixed solution; the mass ratio of aramid fiber to carbon nanotubes is 1:1; the frequency of ultrasonic dispersion is 70 kHz, and the ultrasonic time is 3 h; the ratio of aramid fiber to deionized water is 1 g:300 mL;
[0090] (3) preparing an initial hydrogel by subjecting the mixed solution to a steam bath; and exchanging the solvent of the initial hydrogel with deionized water to obtain a hydrogel; the steam bath is an acetic acid steam bath, and the steam bath treatment time is 8 hours;
[0091] (4) The hydrogel was freeze-dried at -40 °C and crushed to obtain ANF / CNT gel powder.
[0092] Comparative Example 1
[0093] An ANF / CNT gel powder modified cement paste material, wherein the mass ratio of cement, ANF / CNT gel powder, water reducing agent and water in the cement paste is 100:1:0.5:46;
[0094] The preparation method of the ANF / CNT gel powder comprises the following steps:
[0095] (1) placing aramid fiber in a reaction kettle containing alkali and dimethyl sulfoxide, stirring evenly, and preparing an aramid nanofiber dispersion; the alkali is potassium hydroxide; the ratio of the aramid fiber, the alkali and the dimethyl sulfoxide is 1 g:1.6 g:450 mL; stirring is performed at room temperature for 8 days at a stirring rate of 500 r / min;
[0096] (2) Deionized water was first added to the aramid nanofiber dispersion, and then carbon nanotubes were added, and ultrasonic dispersion was performed to obtain a mixed solution; the mass ratio of aramid fiber to carbon nanotubes was 1:0.4; the frequency of ultrasonic dispersion was 70 kHz, and the ultrasonic time was 3 h; the ratio of aramid fiber to deionized water was 1 g:300 mL;
[0097] (3) preparing an initial hydrogel by subjecting the mixed solution to a steam bath; and exchanging the solvent of the initial hydrogel with deionized water to obtain a hydrogel; the steam bath is an acetic acid steam bath, and the steam bath treatment time is 8 hours;
[0098] (4) The hydrogel was freeze-dried at -40 °C and crushed to obtain ANF / CNT gel powder.
[0099] Comparative Example 2
[0100] An ANF / CNT gel powder modified cement paste material, wherein the mass ratio of cement, ANF / CNT gel powder, water reducing agent and water in the cement paste is 100:1:0.5:46;
[0101] The preparation method of the ANF / CNT gel powder comprises the following steps:
[0102] (1) placing aramid fiber in a reaction kettle containing alkali and dimethyl sulfoxide, stirring evenly, and preparing an aramid nanofiber dispersion; the alkali is potassium hydroxide; the ratio of the aramid fiber, the alkali and the dimethyl sulfoxide is 1 g:1.6 g:450 mL; stirring is performed at room temperature for 8 days at a stirring rate of 500 r / min;
[0103] (2) Add carbon nanotubes to the aramid nanofiber dispersion, disperse by ultrasonication, and then add deionized water to obtain a mixed solution; the mass ratio of aramid fiber to carbon nanotubes is 1:0.4; the frequency of ultrasonic dispersion is 70 kHz, and the ultrasonic time is 3 h; the ratio of aramid fiber to deionized water is 1 g:300 mL;
[0104] (3) directly adding acetic acid solution to the mixed solution to obtain an initial hydrogel; and exchanging the solvent of the obtained initial hydrogel with deionized water to obtain a hydrogel;
[0105] (4) The hydrogel was freeze-dried at -40 °C and crushed to obtain ANF / CNT gel powder.
[0106] The mechanical properties of cement paste are tested according to GB / T 50081-2019; the shrinkage rate of cement paste is tested according to GB / T 50082-2009.
[0107]
[0108] Figure 1 This is a transmission electron micrograph of the internal curing agent prepared in Example 7; Figure 1 It shows that by combining alkali modification and ultrasonic treatment, carbon nanotubes are added to the aramid nanofiber dispersion. Under the action of ultrasound, the gradually dispersed modified carbon nanotubes can effectively isolate and disperse the aramid nanofibers prepared by the alkali / DMSO immersion method. The aramid nanofibers also have a crack structure, which makes the carbon nanotubes and aramid nanofibers entangled with each other to form an interpenetrating network structure. Figure 2 and Figure 3And Table 1 shows that carbon nanotubes and aramid nanofibers can cross-penetrate and mechanically entangle with each other to form an interpenetrating network structure, thereby improving the mechanical strength of the material, and on the basis of further improving the porosity of the gel, improving its water release shrinkage, and promoting the stability of the gel structure. Moreover, after being corroded by alkali solution, a portion of water will be retained inside the carbon nanotubes, so that the carbon nanotube and aramid nanofiber gel powder can fully play the role of the internal curing agent, and by increasing the relative humidity inside the cement, the self-drying shrinkage of the cement is minimized. In Comparative Example 1, water is added first, which not only fails to effectively corrode the carbon nanotubes, but also the water added first causes the aramid nanofibers to merge under the action of static electricity, affecting the mechanical and water retention properties of the gel. In Comparative Example 2, gel powder is prepared by directly adding a protonated solvent, resulting in an uneven gelation process, a reduced gel porosity, and an unfavorable improvement in water retention properties.
[0109] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.
[0110] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.
Claims
1. An ANF / CNT gel powder modified cement paste material, characterized in that: The cement paste includes cement and ANF / CNT gel powder; The preparation method of the ANF / CNT gel powder comprises the following steps: (1) placing aramid fiber into a reaction kettle containing alkali and dimethyl sulfoxide and stirring the mixture to prepare an aramid nanofiber dispersion; (2) adding carbon nanotubes to the aramid nanofiber dispersion, dispersing by ultrasonication, and then adding deionized water to obtain a mixed solution; the mass ratio of aramid fiber to carbon nanotubes is 1:(0.2-1); (3) subjecting the mixed solution to a steam bath to obtain an initial hydrogel; and subjecting the obtained initial hydrogel to a solvent exchange with deionized water to obtain a hydrogel; the steam bath is an acetic acid steam bath, a hydrochloric acid steam bath, a formic acid steam bath or a nitric acid steam bath, and the steam bath treatment time is 6-10 hours; (4) The hydrogel is freeze-dried and crushed to obtain ANF / CNT gel powder.
2. The ANF / CNT gel powder modified cement paste material according to claim 1, characterized in that: The stirring rate in step (1) is 400-600 r / min.
3. The ANF / CNT gel powder modified cement paste material according to claim 1, characterized in that: The aramid fiber in step (1) is DuPont Kevlar fiber.
4. The ANF / CNT gel powder modified cement paste material according to claim 1, characterized in that: In the step (1), the alkali is sodium hydroxide or potassium hydroxide; the ratio of the aramid fiber, the alkali and the dimethyl sulfoxide is 1 g: (1-2) g: (400-500) mL; and the stirring is carried out at room temperature for 4-8 days.
5. The ANF / CNT gel powder modified cement paste material according to claim 1, characterized in that: In the step (2), the mass ratio of aramid fiber to carbon nanotube is 1:(0.2-0.5); the carbon nanotube is a single-walled carbon nanotube or a multi-walled carbon nanotube.
6. The ANF / CNT gel powder modified cement paste material according to claim 1, characterized in that: The frequency of ultrasonic dispersion in step (2) is 60-80 kHz, and the ultrasonic time is 2-4 hours; the ratio of aramid fiber to deionized water is 1 g: (250-300) mL.
7. The ANF / CNT gel powder modified cement paste material according to claim 1, characterized in that: The freeze-drying temperature in step (4) is -20°C to -60°C.
8. The ANF / CNT gel powder modified cement paste material according to claim 1, characterized in that: Cement paste also includes water and a water reducing agent.
9. The ANF / CNT gel powder modified cement paste material according to claim 8, characterized in that: The water reducer is a polycarboxylate water reducer.
